Kesejahteraan Spiritual Keluarga Pasien Stroke dan Kaitannya dengan Depresi - Muhamad Zulfatul A’la; Komarudin Komarudin; Defi Efendi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Stroke is a one of major problem in palliative care. Spiritual and depression assessment of the family is an important element in the process of palliative care for stroke survivors. The purpose of this study was to know the description of the spiritual well-being among stroke family caregiver family and its relationship with depression. This study used cross-sectional design. Spiritual well-being scale (SWBS) was used to see the spiritual well-being of the family and the Center for Epidemiologycal Studies Depression Scale (CES-D) to measure depression and was filled in by 44 Stroke families. The results of the study reported that the spiritual well-being of stroke family caregiver was in the high category and depression in the medium category. There was a relationship between the spiritual well-being of the family and depression in stroke patients (p=0.000). This study suggest a comprehensive assessment of the spiritual well-being and depression in stroke family and the need for future research about family interventions to decrease depression and increase spiritual well-being.